Employee Engagement in the Era of Remote Work: Strategies for Innovation and Productivity - Shokrollahi, Nozar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this study is to explore the dynamics of employee engagement in remote work settings and to identify strategies that enhance both productivity and well-being outside the conventional office environment. Methodology: This qualitative study utilized semi-structured interviews to gather data from 25 participants representing various industries, job roles, and geographical locations. Participants were selected using purposive sampling to ensure a broad spectrum of insights. The study aimed for theoretical saturation and utilized NVivo software for the transcription, coding, and thematic analysis of interview data. Findings: Three main themes were identified as critical to enhancing engagement and productivity in remote work settings: Communication Practices, Work-Life Balance, and Employee Support. Each theme comprised several categories: Communication Practices included Team Interaction, Managerial Communication, Tools and Technologies, Information Accessibility, and Feedback Loops; Work-Life Balance included Time Management, Physical Workspace, Mental Well-being, and Boundaries Setting; Employee Support included Technical Support, Professional Development, Emotional Support, Leadership Roles, Autonomy and Trust, and Organizational Culture. Conclusion: The study concludes that effective remote work strategies require robust communication practices, a strong support system, and a dedicated focus on maintaining work-life balance. Organizations should prioritize these areas to foster a productive and engaged remote workforce. Implementing structured communication strategies, supporting professional and personal development, and ensuring physical and psychological well-being are paramount for sustaining high levels of engagement in remote work settings.